MAPt: A Rapid Antibiotic Susceptibility Testing for Bacteria in Environmental Samples as a Means for Bioterror Preparedness - Aloni-Grinstein, Ronit; Shifman, Ohad; Gur, David; Aftalion, Moshe; Rotem, Shahar (Frontiers in Microbiology, 2020)
Antibiotic resistance of bio-threat agents holds major concerns especially in light of advances in methods for engineering pathogens with antibiotic resistance. Preparedness means for rapid identification and prompt proper medical treatment are of need in order to contain the event and prevent morbidity and spreading of the disease by properly treating exposed individuals prior to symptoms appearance. Herein, we describe a novel rapid, simple, specific, and sensitive method, named MAPt, which determines antibiotic susceptibility of bio-terror pathogens directly from environmental samples, with no need for any prior isolation, quantification or enrichment steps. As proof of concept, we have used this approach to obtain correct therapeutic antibiotic MIC values for the Tier-1 select agents B. anthracis, Y pestis and F. tularensis spiked in various environmental samples recapitulating potential bioterror scenarios. The method demonstrated efficiency for a broad dynamic range of bacterial concentrations, both for fast-growing as well as slow-growing bacteria and most importantly significantly shortening the time for accurate results from days to a few hours. The MAPt allows to address bioterror agents-contaminated environmental samples, offering rational targeted prophylactic treatment, before the onset of morbidity in exposed individuals. Hence, MAPt is expected to provide data for decision- making personal for treatment regimens prior to the onset of symptoms in infected individuals.